Alterações cardiorrespiratórias de pacientes submetidos à oxigenoterapia hiperbárica - Martinelli, Bruno (2019)
ABSTRACTObjective To evaluate cardiorespiratory alterations due to a single session of hyperbaric oxygen therapy.Method Randomized study with patients: a control group and hyperbaric oxygen therapy. Evaluations occurred in the beginning, during, and after exposure to pure oxygen above atmosphere for 2 hours. Systemic blood pressure, peripheral oxygen saturation, pulse rate, lung volume and lung capacity, and maximal inspiratory and expiratory pressures were evaluated. Peripheral oxygen saturation, pulse rate, and systemic blood pressure were evaluated during the pressurizing in the first hour. Data were evaluated by means of ANOVA, Mann-Whitney, and independent t-test (p<0.05).Results A total of 14 adult patients were evaluated. In the group under therapy (seven subjects), aged: 49.57±14.59 years, there was a decrease in the pulse rate of 16 beats per minute after 35 minutes of therapy (intragroup analysis), and the peripheral oxygen saturation was higher within the same period compared to the control group.Conclusion The hyperbaric oxygen therapy promotes cardiorespiratory alterations with the increase of the peripheral oxygen saturation and decrease of the pulse rate, without altering blood pressure levels and the strength, volumes, and respiratory capacities.